PERKEMBANGAN DAN TANTANGAN IMPLEMENTASI AKUNTANSI KARBON DI INDONESIA - Pupsitsari, Emilia; Nawangsari, Ajeng Tita (Program Studi Akuntansi Universitas Flores, 2026)
This article examines the key issues underlying the low quality and inconsistency of carbon accounting practices in Indonesia, particularly the absence of national standards, limited technical capacity, and insufficient digital infrastructure to support carbon measurement and disclosure. The study aims to identify the development, challenges, and requirements for implementing carbon accounting by conducting a systematic literature review of publications from 2019 to 2024. The research applies a literature-based approach by analyzing empirical findings, theoretical frameworks, and relevant regulatory developments. The results indicate that carbon disclosures in Indonesia remain predominantly narrative and have not been fully aligned with international standards such as IFRS S2, especially in reporting Scope 2 and Scope 3 emissions. The findings also reveal that the lack of trained human resources, high technological costs, and the absence of uniform national standards pose significant barriers for companies. The implications suggest that harmonizing national standards with global frameworks, strengthening technical and digital capacity, and expanding the national carbon market are crucial to improving carbon accounting quality and supporting Indonesia’s sustainability agenda.